ORGANIZATION OF MULTILEVEL CONTINUOUS ECOLOGICAL EDUCATION - Besik Ch. Meskhi; Larisa E. Pustovaya; Olga V. Dymnikova (Высшее образование в России)
The paper presents the innovative scheme of organization of multilevel continuous environmental education that is being implemented on the basis of the Don State Technical University. This scheme includes such basic structural elements as ecological education of school children and pre-school children, vocational education and student volunteer movement, skills upgrading training, expert activities. There are significant opportunities for self-development, lying in the field of practical volunteer work with the population, including selective collection of hazardous waste generated at home, such as mercury-containing lampsand batteries, as well as in the field of gardening. The proposed scheme can be a model forother educational institutions of Russia, which can provide support for the city authorities in realization of ecological programs of the government of Russia.